Effect of Different Polishing Systems on Surface Roughness of IPS Empress Ceramic Materials - Sara Abdulbasit Turki; Marwah Hussein Abdulsattar; Zahraa Nazar Alwahab (Journal of Techniques)
For evaluation and comparison of the effect of surface treatment (glazings, polishing with rubber wheel and diamond paste, and polishing with rubber wheel) on pressable porcelain (IPS Emax porcelain) surface roughness in comparison with non-treated surface. Forty-disc shaped specimens of baseplate wax with 10 mm diameter and 2 mm thickness have been prepared. They were invested and subjected to lost wax technique in fabricate the pressable ceramic. Following pressing, they have been divided randomly into four groups: Group A: no surface treatments, Group B: glazing (paste, HT, Ivoclar, Vivadent, Germany) glazing (paste, HT, Ivoclar, Vivadent, Germany), Group C: polishing with burs (DIAPRO TWIST, EVE, GmbH, Germany), and Group D: polishing with burs (DIAPRO TWIST, EVE, GmbH, Germany) and diamond paste (All in one, RENFERT, GmbH, Germany). For each specimen, examination of mean roughness profile (Ra) was performed for total surface roughness description. Specimens were stabilized with the acrylic holder used previously in the initial polishing procedure. A contact stylus profilometer was used to conduct a quantitative measurement of surface roughness in micrometers (µm) for all specimens. The highest (Ra) value was for control group (1.9520), whereas the lowest values were in group D (Polishing by rubber wheel .4670. One-way ANOVA test showed a high significant value at (P <. 000), and LSD test showed a high significant value at (P <. 000) when comparison was established among groups. From the results of the current study, we can conclude the following; polishing procedure for the surface of pressable ceramic with or without diamond paste produced better surface smoothness than glazed surface and non-treated surface and polishing with burs could be an alternative to glazing to provide smooth surface.